45 Using simulation training to introduce medical students to COVID-19. Issue Volume 11: Issue (2021)Supplement 1 (16th March 2021) - Rodrigues Cleto, C; Boulstridge, L; Stenhouse, C; Craig, D
Abstract : Introduction: As the COVID-19 pandemic began to surge in the UK, medical students were removed from clinical placements. Consequently many medical students have had little direct experience of managing patients with COVID-19. This study reports, primarily, on a simulation training activity designed to introduce 3rd year medical students to the communication challenges of treating patients with COVID-19. It also reflects upon the benefits to students, of undertaking the role of a simulated patient during training activities. Methods: 21 third year medical students undertook teaching on breaking bad news. A modified SBAR model was taught as a consultation framework. Simulated scenarios, included two patients with COVID-19 and telephone consultations with the patients' families. Students wore surgical masks and undertook the role of doctor and patient or relative. Four students subsequently volunteered to act as simulated patients in training for new foundation doctors. Anonymised questionnaires, utilising ten-point visual analogue scales and qualitative questions, were used to evaluate the training. Results: 95% of students rated their course as excellent overall. High mean visual analogue scores and free-text responses revealed that the training had demonstrated the impact of COVID-19, PPE and restricted visiting on communication and clinical practice. It also informed students about the experiences of clinicians during the pandemic and provided a framework for their first attempts at breaking bad news. Acting as simulated patients was valuable for students' own training and encouraged them to consider the patients' perspectives. Conclusions: The COVID pandemic has had a significant impact upon medical education, causing concern about loss of clinical experience. Consequently a range of innovative teaching models have been reported on worldwide. This study suggests that simulation training can be used effectively to teach medical students about the challenges of clinical management, the complexities of communication and the impact on patients and doctors of COVID-19.